Long-term peritoneal dialysate exposure modulates expression of membrane complement regulators in human peritoneal mesothelial cells - Kobayashi, Kazuma; Ozeki, Toshikazu; Kim, Hangsoo; Imai, Masaki; Kojima, Hiroshi; Iguchi, Daiki; Fukui, Sosuke; Suzuki, Masafumi; Suzuki, Yasuhiro; Maruyama, Shoichi; Ito, Yasuhiko; Mizuno, Masashi (Frontiers in Medicine, 2022)
The membrane complement regulators (CRegs) CD46, CD55 and CD59 are highly expressed on human peritoneal mesothelial cells. However, how mesothelial CRegs change according to the peritoneal dialysis (PD) history of patients has remained unclear. We therefore examined longitudinal changes in CRegs in primary cultured mesothelial cells from PD patients (human peritoneal mesothelial cells; HPMCs) and examined which components of PD fluid (PDF) affect CRegs in vitro. We measured levels of soluble C5b-9 in overnight-dwelling PDF in PD patients and also evaluated changes in CRegs expression on HPMCs collected from PDF using flow cytometry and polymerase chain reaction at a 1-year interval of PD therapy. We also evaluated changes in CReg expressions with stimulation by each component of PDF (glucose, lactic acid and pH) using the Met5A human mesothelial cell line. Levels of sC5b-9 in PDF decreased significantly during 1 year, while expressions of CD46 and CD59 proteins and mRNAs increased significantly in HPMCs during 1 year. Analyzing Met-5A cells, we observed that expressions of the three CRegs were increased by glucose and lactic acid in a concentration-dependent manner, but conversely that expressions of CRegs were decreased by lower pH stimulation. History of PD might influence expression of CRegs by HPMCs through properties of PDF such as glucose, lactic acid, and pH. These results suggest that mesothelial cells may alter expression of CRegs for the purpose of protecting the peritoneum and the presence of PDF might affect peritoneal homeostasis associated with the complement system.